Clinical and imaging evaluation of patients with spontaneous subarachnoid hemorrhage. Observational study of a series of cases. (European Journal of Health Research, 2023)
The clinical and imaging evaluation of patients with spontaneous subarachnoid hemorrhage is a fundamental step in the management and prognostic assessment of these patients. This research aimed to determine the behavior of the initial neurological status and the magnitude (imaging) of bleeding in patients with spontaneous subarachnoid hemorrhage. An observational, descriptive-correlational and retrospective study was carried out, which included 96 patients with spontaneous subarachnoid hemorrhage between 2016 and 2021. The frequencies of the categories of the Hunt and Hess (clinical) and Fisher (imaging) scales were determined; the relationship between these scales and other variables was analyzed using bivariate analysis (Odds Ratio and its confidence interval). Among the results it is found that 54% of the patients were placed in the "grade II" category of the Hunt and Hess scale; only three patients (3%) presented grade V. There was a significant association between the condition of old age and the grouping of grades III-V of said scale (OR 2.6[1.1;6]). 77% of the cases were located in grades III and IV of the Fisher scale, with a predominance of the latter (46%); more than half of the patients 60 years of age or older were classified as grade IV (55%), unlike what was observed in those younger than that age (37%). It is concluded that the series was characterized by the predominance of favorable clinical status on admission, despite high degrees of bleeding according to the Fisher imaging scale. In older adults in particular, greater clinical deterioration was observed upon admission, and greater magnitude of bleeding.
Keywords: cerebrovascular disease; subarachnoid hemorrhage; prognosis